Socio-demographic and health determinants of quality of life among the elderly in Latambaga primary health care area, Kolaka Regency - Heriviyatno J Siagian; Evodius Nasus; Bangu; La Ode Alifariki (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: Quality of life among the elderly is a key indicator of overall well-being and is influenced by physical, social, and economic factors. The growing elderly population is not always accompanied by improvements in quality of life, underscoring the importance of identifying its determinants. Purpose: This study aimed to analyze the determinants of quality of life among the elderly in the working area of the Latambaga Public Health Center, Kolaka Regency. Methods: A cross-sectional study was conducted involving 106 elderly respondents selected using an appropriate sampling technique. Data were collected using standardized questionnaires and analyzed using Chi-square tests and logistic regression with IBM SPSS Statistics version 23 at a 95% confidence level (p < 0.05). Results: More than half of the respondents (56.6%) had a poor quality of life. There were significant associations between social support (p = 0.001), health status (p = 0.002), and economic status (p = 0.047) with quality of life. Multivariate analysis showed that social support was the most dominant factor influencing quality of life (OR = 3.45; 95% CI: 1.62–7.35). Conclusion: Social support, health status, and economic status are significant determinants of quality of life among the elderly, with social support being the most influential factor. Strengthening social support systems is essential to improve the well-being of the elderly.